2020
DOI: 10.1038/s41398-020-01045-4
|View full text |Cite
|
Sign up to set email alerts
|

Defining data-driven subgroups of obsessive–compulsive disorder with different treatment responses based on resting-state functional connectivity

Abstract: Characterization of obsessive–compulsive disorder (OCD), like other psychiatric disorders, suffers from heterogeneities in its symptoms and therapeutic responses, and identification of more homogeneous subgroups may help to resolve the heterogeneity. We aimed to identify the OCD subgroups based on resting-state functional connectivity (rsFC) and to explore their differences in treatment responses via a multivariate approach. From the resting-state functional MRI data of 107 medication-free OCD patients and 110… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 73 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…Our results were also consistent with Kwak and colleagues who indicated that not only within‐DMN rs‐FC but also functional connectivity between brain regions involved in the DMN were critical and that rs‐FC features in somatosensory‐motor, visual and auditory, and cingulo‐opercular networks were associated with clinical symptom severity improvement. (Kwak et al, 2020 ). We also found within State I that connectivity within motor and sensory networks (CB‐AUD, CB‐VIS, SMN‐VIS) was greater in OCD compared with HC.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were also consistent with Kwak and colleagues who indicated that not only within‐DMN rs‐FC but also functional connectivity between brain regions involved in the DMN were critical and that rs‐FC features in somatosensory‐motor, visual and auditory, and cingulo‐opercular networks were associated with clinical symptom severity improvement. (Kwak et al, 2020 ). We also found within State I that connectivity within motor and sensory networks (CB‐AUD, CB‐VIS, SMN‐VIS) was greater in OCD compared with HC.…”
Section: Discussionmentioning
confidence: 99%
“…119 Importantly, predictive modelling avoids issues with multiple comparisons and low statistical power that arise when comparing multivariate data between clinical groups. 119 Indeed, a handful of recent large-scale studies have conducted data-driven analyses using machine-learning algorithms to investigate subtypes of OCD based on resting-state functional connectivity patterns and the extent to which those data-driven subtypes differ in treatment response to CBT, 120 and to investigate homogeneous subgroups of children with OCD, autism, or ADHD based on integrated measures of brain structure and clinical symptomatology. 121,122 These studies indicate that it is possible to identify subgroups within OCD and also across traditional diagnostic categories that are characterized by different neural alterations associated with different clinical profiles 121,122 or reductions in OCD symptoms in response to treatment with CBT.…”
Section: Future Directions: Advancing Neurocircuit Models Of Ocd and Bridging The Gap To Treatmentmentioning
confidence: 99%
“…121,122 These studies indicate that it is possible to identify subgroups within OCD and also across traditional diagnostic categories that are characterized by different neural alterations associated with different clinical profiles 121,122 or reductions in OCD symptoms in response to treatment with CBT. 120 A similar analytical approach is planned for the latest phase of our cross-site global study of OCD; we will apply machine learning methods to ''multi-modal fusion'' data (i.e., combined clinical, neuropsychological, and structural and functional neuroimaging data) to identify brain signatures of OCD. 123 Such data-driven approaches will be important for testing the subgroups of OCD related to underlying neurocircuit dysfunctions proposed in neurocircuit models.…”
Section: Future Directions: Advancing Neurocircuit Models Of Ocd and Bridging The Gap To Treatmentmentioning
confidence: 99%
“…Due to the vast amount of data, the selection of informative features from tremendous neuroimaging data is necessary in ML studies that are based on neuroimaging (Chiang et al, 2015) since it decreases the computational burden and improves the performance of SVM models. As in previous study, the twosample t-test (p < 0.005) was used to select features in the current study (Suk et al, 2015;Kwak et al, 2020). After the features with discriminative information were selected, we adopted the Fisher score as the feature weight in the SVC model (Germond et al, 2018), which is defined in the following equation:…”
Section: Svm Modelingmentioning
confidence: 99%